2021
DOI: 10.15275/rusomj.2021.0307
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization Of Autonomic Control Loops Of Blood Circulation In Patients With COVID-19

Abstract: This study aims to investigate the strength of synchronization between the autonomic control loops of the cardiovascular system (CVS) in patients with COronaVIrus Disease 2019 (COVID-19). Methods — We calculated the total percent of phase synchronization index (S index) between the loops of autonomic control of heart rate and vascular tone in two sample groups: healthy individuals and COVID-19 patients. Results — The group-average value of the S index in COVID-19 patients is lower comparing to healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…After removing duplicates, 1585 results remained and were evaluated for title and abstract check. Therefore, 65 reports were considered in the full-text review stage, and 20 of those were included in the systematic review [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], while 45 reports were excluded: 2 papers written in Russian [49,50], 5 conference papers [51][52][53][54][55], 3 comments [56][57][58], 4 case reports or case series [59][60][61][62], 2 literature reviews [63,64], 1 study protocol [65], 12 studies that did not perform a formal evaluation of autonomic functions [66][67][68][69][70][71][72][73][74][75]…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates, 1585 results remained and were evaluated for title and abstract check. Therefore, 65 reports were considered in the full-text review stage, and 20 of those were included in the systematic review [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], while 45 reports were excluded: 2 papers written in Russian [49,50], 5 conference papers [51][52][53][54][55], 3 comments [56][57][58], 4 case reports or case series [59][60][61][62], 2 literature reviews [63,64], 1 study protocol [65], 12 studies that did not perform a formal evaluation of autonomic functions [66][67][68][69][70][71][72][73][74][75]…”
Section: Study Selectionmentioning
confidence: 99%
“…Finally, 22 studies were included in this systematic review [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]94,95]. Details regarding the selection process are available in the PRISMA diagram (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, future research should consider assessing both linear and non-linear measures of HRV and BPV, which can be a promising field for exploring autonomic cardiac loops of circulation in MG patients. Several studies have shown that such methods were useful tools for clinical practice, in particular, in patients with cardiovascular events (hypertension, myocardial infarction) [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%